Torres pensantes : ¿Habrá terminado la era del expresionismo de las máquinas? - Corona Martínez, Alfonso (1996)
Torre Bourchard y Fortabat. Dirección de obra: <Peralta Ramos-SEPRA>
Keywords: EDIFICIOS INTELIGENTES; BUENOS AIRES; ARGENTINA; SEPRA; PUERTO MADERO